Case series of synovial chondrosarcoma of the knee joint: A very rare but challenging differential diagnosis in benign synovial lesions (Indian Journal of Case Reports, 2020)
Synovial chondrosarcoma (SCH) is a very rare malignancy and its differentiated from benign synovial lesion such as pigmented villonodular synovitis (PVNS) and synovial chondromatosis (SC) is challenging but crucial. Here, we present a case series of two different cases of 44 and 47 years old men with unilateral knee pain and swelling for the past 3 and 2 years, respectively. The knee gradually swells more in both cases. The medical history and constitutional symptoms were negative. There was a mass with a size of nearly 3 × 4 cm in the left knee of the first case and nearly 5 × 5 cm on the same side of the second case. Based on the magnetic resonance imaging and X-Ray, a diagnosis of synovial chondromatosis or PVNS was made. After marginal resection in both cases, the histologic analysis was consistent with the diagnosis of synovial chondrosarcoma. These patients were monitored carefully and both of them are asymptomatic. Although SCH is very rare, its misdiagnosis with PVNS and SC might lead to devastating consequences.